2010
DOI: 10.4028/www.scientific.net/kem.452-453.361
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fatigue Limit by Mono-Axial Tensile Specimens Using Thermal Analysis

Abstract: In this work is indicated how it could be possible to evaluate the limit stress of the thermo-elastic phase of deformation by thermo-analysing the surface of the specimen during a static traction test. Adding the temperature curve measured on a small area of the surface (the hottest) to the classic stress-strain curve, it is possible to evaluate a limit temperature T0 coincident with the beginning of the non linear trend of the curve. The corresponding stress value is coincident with the fatigue limit of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
(10 reference statements)
2
10
0
1
Order By: Relevance
“…The Tab. 5 and 6 resume the results obtained during the static tests in agreement with [15][16][17][18][19]. In the tables with the caption "material without damage" it has been identified the resistance values provided by the tie rods building firm.…”
Section: Experimental Analysissupporting
confidence: 59%
See 2 more Smart Citations
“…The Tab. 5 and 6 resume the results obtained during the static tests in agreement with [15][16][17][18][19]. In the tables with the caption "material without damage" it has been identified the resistance values provided by the tie rods building firm.…”
Section: Experimental Analysissupporting
confidence: 59%
“…In the tables with the caption "material without damage" it has been identified the resistance values provided by the tie rods building firm. Specimen 2 of an old tie rod 420 Table 6: Results using the [15][16][17][18][19] theory.…”
Section: Experimental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first analyses of this type which date back to 1987, it has been noted that, using this approach, it was possible to determine the region (stress-strain) in which the material follows the laws of the Thermoelasticity [38,39]. The Thermal analysis applied to various steels during the static tensile test [29][30][31][32][33][34], showed that it was possible to define the "fatigue limit" by analyzing the temperature of the hottest point of the specimen surface and determining the point where the slope changes, in the temperature vs. stress curve. On the basis of the first results, other researchers [35,36] tested the procedure on other materials, different from the steels (composite materials).…”
Section: Introduction and Aim Of The Workmentioning
confidence: 99%
“…And in [15] have investigated experimentally on thermal and calorimetric effects induced by Luders band propagation during monotonic and quasi-static tensile tests. In previous papers, authors investigated the variation of temperature during static tensile tests of plastic [16] and metallic [17] materials to connect the variation of the slope of the stress strain versus temperature curve with the conventional fatigue limit of the material. In [18], authors suggested that during quasi-static tensile tests the area, where first irreversible plasticization occurred, is detectable on T vs curve by the variation of temperature (slope).…”
Section: Introductionmentioning
confidence: 99%